Influence of Humidity on Contact Resistance in Graphene Devices - Quellmalz, Arne (ACS Appl Mater Interfaces, 2018)
[Image: see text] The electrical contact resistance at metal–graphene interfaces can significantly degrade the properties of graphene devices and is currently hindering the full exploitation of graphene’s potential. Therefore, the influence of environmental factors, such as humidity, on the metal–graphene contact resistance is of interest for all graphene devices that operate without hermetic packaging. We experimentally studied the influence of humidity on bottom-contacted chemical-vapor-deposited (CVD) graphene–gold contacts, by extracting the contact resistance from transmission line model (TLM) test structures. Our results indicate that the contact resistance is not significantly affected by changes in relative humidity (RH). This behavior is in contrast to the measured humidity sensitivity [Image: see text] of graphene’s sheet resistance. In addition, we employ density functional theory (DFT) simulations to support our experimental observations. Our DFT simulation results demonstrate that the electronic structure of the graphene sheet on top of silica is much more sensitive to adsorbed water molecules than the charge density at the interface between gold and graphene. Thus, we predict no degradation of device performance by alterations in contact resistance when such contacts are exposed to humidity. This knowledge underlines that bottom-contacting of graphene is a viable approach for a variety of graphene devices and the back end of the line integration on top of conventional integrated circuits.